KLASIFIKASI PENAMPILAN WAJAH PADA RATA-RATA WANITA ACEH MENGGUNAKAN METODE TEMPLATE MATCHING DAN HAMMING DISTANCE - Deassy Siska; Hayatul Muslima (Teknik Informatika Universitas Malikussaleh, 2015)
The appearance of the face is very overlooked for most people often talk about and especially the problem of beauty. Beauty itself is a theme that full debate because beauty itself very closely related to of experience situation, or where the state of social attributes the beauty will be defined, in other words that judgment would be pretty or not someone has beautiful very relative to the values agreed on by this community. Research task at this final writer want to make a system of classification the appearance of the face. Classification process appearance this face using method Template Matching and Hamming Distance.In this research video used was in .avi 24 bits, And real-time. The result of this research is to make in some classification systems the appearance of the face with three classifications namely